How Do Small Formal and Informal Firms in the Arab Republic of Egypt Compare? - Krafft, Caroline; Assaad, Ragui; Rahman, Khandker Wahedur; Cumanzala, Maakwe (World Bank, Washington, DC, 2020)
Formalizing firms can potentially increase the tax base, expand safety and social protections for workers, create good jobs, and grow the economy. However, the costs and processes of formality may be too challenging for firms, particularly the smallest firms, to bear. Thus, informal firms may not be able to survive the transition to formality and attempts to expand formality may be harmful and counterproductive to job creation and growth. This paper investigates the potential for currently informal firms to formalize in the Arab Republic of Egypt. The paper compares the characteristics and dynamics of micro and small non-agricultural firms by formality and identifies the extent of overlap and potential for formalization. The analysis finds that, beyond firm size, the basic and easily observable characteristics of firms are not closely linked to formality. Firm age, productivity, and owner characteristics such as education are strongly predictive of formality. There is some overlap in the predicted probability of formality between formal and informal firms, suggesting some potential for formalization. The paper develops profiles (groups and clusters) of similar firms to identify those with a higher potential for formalization. In terms of dynamics, new firms tend to be informal and informal firms are more likely to exit (close), but conditional on firm survival, employment growth is similar across formal and informal firms.